A Study of the Relationships Between some variables and Student Achievement on the TIMSS-2019 International Study in the Kingdom of Saudi Arabia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The results of the TIMSS study showed that the average achievement of students in the Kingdom of Saudi Arabia in mathematics is lower than the international average. Student achievement in learning is affected by different variables such as characteristics of the student, teacher training and qualifications, as well as the school. As such, this study aims to determine the reason for student low achievement in mathematics using the data of the TIMSS study of 2019. Detailed data is provided about these variables through the student's questionnaire, the teacher's questionnaire, and the school's questionnaire. The study found that a positive relationship exists between the gender variable and student outcomes/achievement in the study of mathematics. The study also found that computational skills could aid students’ learning such that they would have the mental capacity to perform and achieve in mathematics and other science subjects.